O uso do computador no processo de ensino e aprendizagem: questões de representação social - Silva, Analigia Miranda da [UNESP]; Lima, Claudia Maria [UNESP] (Universidade do Estado de Santa Catarina, 2013)
This paper presents the results of a study aimed at identifying and analyzing the theoretical and methodological principles that guide the practice of teachers in the early years of computer use in the teaching and learning. Specific objectives we seek to identify and analyze the social representations of teachers on the use of computers in teaching and learning. The research took a qualitative approach with a descriptive-explanatory and owned two phases of data collection: a) a questionnaire b) monitoring the daily practice of teachers in a selected school and semi-structured interview. The analysis of data was done through content analysis. Through the interrelationship of the data in the questionnaire, observation and interview, we found that the teachers surveyed have an address that does not match the teaching practice in the use of computers in the educational process. The theoretical expressed by teachers participating in the research meets constructivist beliefs and / or sociointeractionists but teaching practice thins primarily to behavioral assumptions. Observe social issues of representation when the speeches of the participating teachers did not correspond to their practices. Associated with this or as a cause of these conditions have failure, inadequacy or absence of teacher training for the use of computers in the educational process leading to under-utilization of this resource.

Este trabalho apresenta os resultados de uma pesquisa que teve por objetivo geral identificar e analisar os pressupostos teóricometodológicos que norteiam a prática de professores dos anos iniciais no uso do computador no processo de ensino e aprendizagem. Como objetivo específico, busca identificar e analisar as representações sociais dos professores sobre o uso do computador no processo de ensino e aprendizagem. A pesquisa assumiu abordagem qualitativa com delineamento descritivoexplicativo e possuiu duas fases de coleta de dados: a) aplicação de questionário; b) acompanhamento da prática cotidiana dos professores de uma escola selecionada e entrevista semiestruturada. A análise dos dados se deu mediante análise de conteúdo. Por meio da inter-relação dos dados presentes no questionário, da observação e da entrevista, constatamos que os professores pesquisados apresentam um discurso que não coincide com a prática docente no uso do computador no processo educativo. O aporte teórico expresso pelos professores participantes da pesquisa vai ao encontro de pressupostos construtivistas e/ou sociointeracionistas, mas a prática docente se afina, prioritariamente, a pressupostos comportamentalistas. Observamos questões de representação social quando os discursos dos professores participantes não correspondem às suas práticas. Associado a isso, ou como causa dessas condições, temos a insuficiência, a inadequação ou a ausência de formação docente para o uso do computador no processo educativo, que levam à subutilização desse recurso.
The use of computer in the process of teaching and learning: issues of social representation
Keywords: Práticas Pedagógicas; Computador; Representação; Social; Pedagogical Practices; Computer; Social Representation